(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The purpose of this investigation was to document the body composition elements’ changes, preparing an initial precompetition and postcompetition training programme of soccer players. Body composition measurements were taken 10 weeks prior to competition, at 2 hours before competition and 4 weeks after competition period (week 14). There were investigated: body height (BH), body mass (BM), body mass index (BMI), body fat mass (BFM), fat free body mass (FFBM), fat free body mass index (FFBMI), body water mass (BWM), water free body mass (WFBM), water free body mass index (WFBMI). Body mass, the percent age of BFM and BWM at all body mass was calculated using the whole body bioelectrical impedance analysis (BIA) with “Tanita” monitor (Japan). Body mass and body composition values of soccer players varied at precompetition, competition and postcompetition periods. The decreased body mass at competition period by 8.16% is the result of lost body fat mass and body water mass. Fat free body mass index (FFBMI) and water free body mass index (WFBMI) indicate, that soccer players at precompetition and competition period did not use lean tissue, that positively related to the restoration of body composition and water balance at postcompetition period. Keywords: body composition, body mass, body fat mass, body water mass.